Smart and structural thermosets from the cationic copolymerization of a vegetable oil - Meiorin, Cintia (2012)
Copolymers based on tung oil (TO) and presenting a very wide range of properties were obtained. Depending on the chemical composition, materials fitted for structural or functional applications were prepared. The use of divinylbenzene (DVB) as a comonomer in the cationic polymerization of the triglyceride allowed us to obtain polymers with a high thermal stability in an ample temperature range and with a room-temperature modulus close to 1 GPa for percentages of TO up to 40 wt % styrene (St) as a partial replacement of DVB in a copolymer containing 50 wt % TO resulted in a material with shape-memory behavior with switch temperatures in the range 25-40°C. The mechanical properties and shape-memory behavior of copolymers with different chemical compositions were analyzed. It was observed that an increase in the DVB content increased the glass-transition temperature and modulus, which was associated with an increase in the crosslinking density and the contribution of the rigid aromatic structure of the comonomer.